KEBIJAKAN LEGALISASI ASET TANAH MELALUI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KOTA PEKANBARU (STUDI PADA KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI) TAHUN 2021 - Setyawati, Ajeng; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
PTSL is the activity of registering land for the first time carried out simultaneously for all objects of land registration throughout the territory of the Republic of Indonesia in one village/urban village or other name at the same level, which includes the collection of physical data and juridical data regarding one or several objects. land registration for the purposes of its registration. The large number of land parcels that have not yet been registered and mapped in Indonesia and the slow process of land certification is the background for the establishment of a complete systematic land registration program (PTSL). The actors involved in this program are required to implement PTSL professionally which refers to legal and technical provisions so that there is no practice of maladministration. Thus being the reasons for this research that aims to investigate the policy of land asset legalization through the Complete Systematic Land Registration Program (PTSL) in Pekanbaru City in 2021, as well as the factors influencing the policy of land asset legalization through the Complete Systematic Land Registration Program (PTSL) in Pekanbaru City in 2021. This research refers to the theory from George Edwards III (1980) with qualitative approach. Data collection techniques involving interviews and documentation. The data analysis techniques used include data reduction, data presentation, and drawing conclusions. The research of the results show that in terms of target achievement, the land asset legalization policy through the Comprehensive Land Registration System (PTSL) in 2021 in Pekanbaru City has not yet achieved the set targets. Overall, the land asset legalization policy through the Comprehensive Land Registration System in Pekanbaru City has not been well implemented, due to several challenges such as insufficient intensive counseling from the Pekanbaru Land Agency (BPN), insufficient human resources and manpower, frequent bribery by the Maharatu Subdistrict Government, and inadequate coordination with cross-sector stakeholders like the Ministry of Environment and Forestry, Village Defense Corps (Babinsa), and other stakeholders involved. Keyword: Land Legalization, Comprehensive Land Registration System (PTSL), National Land Agency (BPN)